1995
DOI: 10.1002/aja.1002030409
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte apoptosis in endochondral ossification of chick sterna

Abstract: In the process of endochondral ossification, chondrocytes progress through a series of maturational changes, including division and hypertrophy, that culminate in chondrocyte loss and cartilage resorption. From an investigation of morphology, DNA fragmentation, and collagen synthesis in the developing chick sterna we have characterized chondrocytes death in this process. Light microscopy of resorbing sterna demonstrated chondrocyte condensation at the interface with the invading vasculature and electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
2
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 35 publications
5
95
2
3
Order By: Relevance
“…Investigations into the removal of cells from the chondro-osseous J. L. Ford et id. I Journal .f Orthopuedic Reseurch 21 (2003) 54-61 5.5 junction in growth plate tissue have shown that terminal hypertrophic chondrocytes are removed from the epiphysis via apoptosis, which plays an important role in the ossification process [8,10,33]. Significantly higher levels of apoptosis have been observed in osteoarthritic cartilage compared to healthy cartilage [9,11,13,181 The precise mechanisms involved in chondrocyte loss from the soft callus have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the removal of cells from the chondro-osseous J. L. Ford et id. I Journal .f Orthopuedic Reseurch 21 (2003) 54-61 5.5 junction in growth plate tissue have shown that terminal hypertrophic chondrocytes are removed from the epiphysis via apoptosis, which plays an important role in the ossification process [8,10,33]. Significantly higher levels of apoptosis have been observed in osteoarthritic cartilage compared to healthy cartilage [9,11,13,181 The precise mechanisms involved in chondrocyte loss from the soft callus have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It is still a point of controversy whether all chondrocytes undergo apoptosis (Farnum and Wilson, 1990;Gibson et al, 1995;Hatori et al, 1995;Bronkers et al, 1996;Aizawa et al, 1997) or whether some survive to become bone-forming cells (Cancedda et al, 1995;Roach et al, 1995). Using morphological criteria, any chondrocyte with a condensed nucleus is often considered unviable or apoptotic.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, chondrocytes first proliferate and then differentiate into mature hypertrophic chondrocytes, which mineralize the surrounding matrix that is finally replaced by bone (1). There is controversy as to the cell fate of hypertrophic chondrocytes, and several studies have shown that they undergo apoptosis after terminal differentiation (2)(3)(4). Apoptosis is a form of programmed cell death that is characterized by specific morphological and biochemical features, and is tightly regulated by extracellular stimuli and intracellular signaling pathways (5).…”
mentioning
confidence: 99%